ASSESSMENT OF GENETIC DIVERSITY AMONG SOME IMPORTANT WILD SPECIES OF NON – TUBEROUS SOLANUM USING RAPD AND ISSR MARKERS - AJOY KUMAR DAS; SAILENDRA PRASAD BORAH (International Journal of Pharma and Bio Sciences, 2015)
Random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) markers were used for assessing genetic diversity and species relationships among eight species of Solanum. Both random and SSR primers revealed 90.9 and 96.1 % polymorphism, respectively. ISSR markers were found to be more efficient than the RAPD assay. The marker index and polymorphic information content varied from 40.8 - 47.0, 40.9- 49.0 and 0.41 -0.49, 0.43-0.49 respectively for both the RAPD and ISSR markers. Mean value of number of observed alleles, number of effective alleles, Nei’s gene diversity and Shannon’s index were 1.95-1.99, 1.47-1.75, 0.26-0.37 and 0.45-0.43 respectively for both the markers. Both UPGMA and PCA analyses of the data revealed clear groupings among the species. Genetically distinct genotypes identified by using RAPD and ISSR markers could be potential sources of germplasm for conservation and further improvement of the genus Solanum.